A Confinement Strategy for Stabilizing ZIF‐Derived Bifunctional Catalysts as a Benchmark Cathode of Flexible All‐Solid‐State Zinc–Air Batteries. Issue 45 (27th September 2018) - Zhu, Lin; Zheng, Dezhou; Wang, Zifan; Zheng, Xusheng; Fang, Pingping; Zhu, Junfa; Yu, Minghao; Tong, Yexiang; Lu, Xihong
Abstract: Carbon composites with embedded metal/metal oxides represent a group of versatile electrochemical catalysts that has attracted extensive research attention. However, the beauty of this concept is marred by the severe carbon evaporation and the aggregation of metal species during their synthetic process, leading to the diminishment in active sites and catalytic durability. To address this issue, this study demonstrates the feasibility of utilizing Al2 O3 nanolayer to trap volatile carbon and nitrogen species and alleviate the aggregation of Co species during the pyrolysis of the Zn/Co‐ZIFs (ZIF = zeolitic imidazolate framework). With the confinement effect of an Al2 O3 nanolayer, the derived Co3 O4 ‐embedded N‐doped porous carbon grown on carbon cloth presents outstanding bifunctional catalytic activity with a small potential difference of 787 mV between the half‐wave potential of the oxygen reduction reaction and an overpotential at 10 mA cm −2 of the oxygen evolution reaction. More impressively, an advanced flexible rechargeable zinc–air battery in all‐solid‐state configuration is assembled, which achieves the maximum power density of 72.4 mW cm −3 and good cycling stability. The insights produced in this work will provide guidance for the rational design of metal/carbon hybrid catalysts and low‐cost renewable energy systems. Abstract : A novel confinement strategy is developed to stabilize the structure and active sites of Zn/Co‐ZIF‐derived catalysts by uniformly depositing an Al2 O3 nanolayer. The derived catalyst with well‐preserved polyhedron structure presents outstanding bifunctional catalytic activity, which is further employed to assemble advanced flexible rechargeable zinc–air batteries.